Quality of life in the postpartum period of Mexican women living with HIV: The role of clinical and sociodemographic factors - Mauricio Domínguez-Castro; Alicia Ramírez-Ramírez; Noemí Guadalupe Plazola-Camacho; Miroslava Avila-García; Edna Basilio-Gálvez; Margarita López-Martínez; Lucky Norah Katende-Kyenda; Ismael Mancilla-Herrera; Diana Mercedes Soriano-Becerril; José Romo-Yáñez; Carmen Selene García-Romero; Ricardo Figueroa-Damián; et al. (PLoS ONE, 2026)
Introduction The HIV epidemic remains a major public health challenge, specifically for women living with HIV who face vulnerabilities during pregnancy and motherhood. Furthermore, high vulnerability is closely linked to a lower quality of life. It is essential to address the determinants that influence quality of life within this population in order to enhance health outcomes and inform the development of evidence-based care protocols. Methods An observational, cross-sectional study was conducted from 2020 to 2022 to assess the quality of life of Mexican postpartum women living with HIV (n = 75). The WHOQoL-HIV-Bref instrument was used. Quality of life results were analysed statistically in relation to sociodemographic and clinical factors to evaluate their associations and their predictive power through multinomial logistic regression analysis. Results Nearly half of postpartum WLWH experienced a lower quality of life (49%). Psychological health, Environment, Spirituality, religion and personal beliefs domains scores were below the median. There were multiple associations with socio-demographic and clinical factors. Highlights the use of ART during pregnancy and postpartum, HIV symptoms, sexual behavior, marital and educational status, mainly. Physical health, Independence level, and Spirituality, religion and personal beliefs domains were identified as potential predictors of a perception of high quality of life of this population. Conclusion There are clinical and socio-demographic factors that influence the perception of quality of life in Mexican women living with HIV during postpartum. It is important to identify and mitigate these factors for the well-being of these women and their children. Further research is needed to evaluate the impact of interventions on Physical health, Independence level, and Spirituality, religion and personal beliefs domains to improve perception of high quality of life in WLWH. These findings ultimately underscore the need to integrate quality of life assessment as the fourth ‘95’ target in World Health Organization strategies for people living with HIV.